MRS DALLOWAY: VIRGINIA WOOLF'S REDEMPTIVE CYCLE - Howard, Douglas L. (Literature and theology, 1998)
This paper examines the extent to which Mrs Dalloway is pervasively influenced by the Bible and juxtaposes a pattern of Biblical history with the contemporary history that is created within the course of the novel. From the recollections of that summer at Bourton to Septimus' death and Clarissa's party, Edenic beginnings are nostalgically remembered, the ‘fall’ into adulthood is painfully recalled, and, through the sacrifices of a number of unlikely 'Chnsts and Christesses', rebirth and spiritual renewal are ultimately achieved. Although she is often portrayed as an author without any apparent interest m Christianity, Woolf uses these motifs not only so as to give her story mythic importance, but also, through her creative implementation of this metaphor, so as to mark her break from patriarchal Christian values and redefine the character of her own beliefs.